If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (f + -8)(8f + -5) = 0 Reorder the terms: (-8 + f)(8f + -5) = 0 Reorder the terms: (-8 + f)(-5 + 8f) = 0 Multiply (-8 + f) * (-5 + 8f) (-8(-5 + 8f) + f(-5 + 8f)) = 0 ((-5 * -8 + 8f * -8) + f(-5 + 8f)) = 0 ((40 + -64f) + f(-5 + 8f)) = 0 (40 + -64f + (-5 * f + 8f * f)) = 0 (40 + -64f + (-5f + 8f2)) = 0 Combine like terms: -64f + -5f = -69f (40 + -69f + 8f2) = 0 Solving 40 + -69f + 8f2 = 0 Solving for variable 'f'. Factor a trinomial. (5 + -8f)(8 + -1f) = 0Subproblem 1
Set the factor '(5 + -8f)' equal to zero and attempt to solve: Simplifying 5 + -8f = 0 Solving 5 + -8f = 0 Move all terms containing f to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -8f = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -8f = 0 + -5 -8f = 0 + -5 Combine like terms: 0 + -5 = -5 -8f = -5 Divide each side by '-8'. f = 0.625 Simplifying f = 0.625Subproblem 2
Set the factor '(8 + -1f)' equal to zero and attempt to solve: Simplifying 8 + -1f = 0 Solving 8 + -1f = 0 Move all terms containing f to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1f = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1f = 0 + -8 -1f = 0 + -8 Combine like terms: 0 + -8 = -8 -1f = -8 Divide each side by '-1'. f = 8 Simplifying f = 8Solution
f = {0.625, 8}
| 7x+3-2x+9-5x=19 | | (1+2i)(1-2i)=0 | | 2.25=-2.67x-1.83x | | 8a+11=3a+41 | | x+7.7=33 | | (r-8)(r+1)=0 | | x-25=-65 | | 6(r-4)=-5r+31 | | y=10x^4-360x^2 | | (k-8)(k+2)=0 | | x^2+bx+c=r | | v+5.5=31.1 | | 4.3t-2.1t-0.2c=7.6 | | 3(4x+7)=9x-3 | | 5z-23=-41+3z | | (z+7)(4z+9)=0 | | 8x-30+6x+84=180 | | 4(3x+2)-3= | | 1.3+v=5.3 | | 5z-23=-41+32 | | 2x^2+2y^2-20x-16y-16=0 | | 2.6x+1.17-3.4=5.2 | | 6+3y-3=7y+5-5y | | 3(6x+2)-18x=12 | | 5x+3=9x+21 | | (4h+9)(h-4)=0 | | (12+5i)-(9-2i)=0 | | 1.3+5.3=24.2 | | 2(-4y+4)+8y=8 | | 9x^2-30x-525=0 | | 3r-14=-28+r | | -90=9x |